Radiometric measurements of spine and pelvis among patients - Gasik, Robert; Styczyński, Tadeusz (Reumatologia/Rheumatology, 2007)
The purpose of the study was an attempt to determine a connection between chosen parameters of the pelvic structure on x-ray pictures taken in a standing position from the side and chosen features of the course of back pain. We were particularly interested in measurements determining a mutual relationship between the sacral bone and hip joints. The measurement results were compared in a group of patients suffering up to 3 years and over 4 years. All patients evaluated for examination constituted a group of 152 people. After conducting statistical analysis it was found that the angle 3 (pelvic morphology) defining sacral bone inclination in relation to the axis running through the hip joint heads was bigger among patients suffering longer. Other measured parameters, including lumbar lordosis and sacral bone inclination in relation to the horizontal line, did not differ between the groups examined. Taking into consideration the fixed value of angle 3 individually, it is to be deduced that patients with a large angle are more subject to chronic back pain than patients with a smaller angle.